(3fRgI GdCdHG aj WHbGJ GdCOHG (B( (3ef GdfMhjjf(B)s - (3YHO GdQMef Hf eMeO Hf YHjO Gddg GdCfUGQj , GHf GdCfHGQj, ceGd GdOjf CHh GdHQcGJ,J (B577 (3g` s
(3ChdgG (B:s
(3hHYO , abO PcQJ ai gPG GdcJGH GdehShe HfRgI GdCdHG ai WHbGJ GdCOHG eYGQa gPg GdUfGYI GdCYjGf hef bGQHge ai GdeYQaI hGdEJbGf s
(3BNQgG (B:s
(3HBNQg JbjjOGJ ef cJH CNQi ENJdWJ HBNQ GdcJGH s
(3ai HYV UaMGJgG HjGVs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B183 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B519s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B282 ; (3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B495 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B446 s
Keywords: (3GdJGQjNs